ENT600 : Parents Care Sdn. Bhd. X-tube breast pump / Mohamad Izwan Roselan, Mohd Yusof Mohamed Fahmy and Mohd Akhil Abdul Aziz - Roselan, Mohamad Izwan; Mohamed Fahmy, Mohd Yusof; Abdul Aziz, Mohd Akhil (2018)
Breast milk is amazing. It's life-giving and life-changing. Even in the smallest amounts. We know that moms are committed to breastfeeding-not only for the health benefits but because of the unique bond it creates. This bond is very miracle that can make our generation become a star in their future. The power of breast milk is timeless, but the way moms make breastfeeding work has changed. Our destiny statement reads that we exist to enhance mother and baby health through the life-giving benefits of human milk. We also committed to improving mom's breast milk pumping experience and her ability to successfully provide breast milk to her baby for as long as she chooses. Through intensive dialogue with healthcare professionals, patients, and consumers, we gain intimate understanding of their needs, and transform valuable knowledge into innovative products and services that make feeding with breast milk an easier reality. We try to make our product very friendly user so mom's can experience breast milk pumping very freely without disturbing their job or their lifestyle. We try to become our product as a new style on mom's life and become a needs to their trend. The futuristic function become an easy way to their users, also can monitor their comsumption and the volume or producing. Wisdom from Our Founder "Looking at nature is not a fashion trend, but the most fascinating story ever to be discovered. Spending time to look at natural behavior and then using what you have learned to develop something truly helpful for mother and baby lasts more than a lifetime."